AB0568 Efficacy of abatacept in patients with early (≤6 months) RA: Results from agree post-hoc analysis. (23rd January 2014) - Westhovens, R.; Wollenhaupt, J.; Gomez Reino, J.J.; Grassi, W.; Le Bars, M.; Gaillez, C.; Poncet, C.; Elegbe, A.; Smolen, J.S.
Abstract : Background: Treatment paradigms for RA have shifted, emphasizing earlier intervention with biologics.The AGREE trial was a 2-year, Phase IIIb, multinational study evaluating efficacy and safety of IV abatacept (ABA)+MTX vs placebo (PBO)+MTX in MTX-naive pts with early RA (≤2 years disease duration at baseline [BL]). Objectives: To examine the effect of IV ABA+MTX vs PBO+MTX in a subset of pts from AGREE with very early RA (≤6 mths disease duration at BL) and poor prognostic markers compared with the broader AGREE pt population. Methods: A post-hoc analysis was performed in a subset of pts from AGREE with very early RA (≤6 mths disease duration at BL). In the double-blind period, pts were randomized 1:1 to IV ABA (10 mg/kg, according to weight range) or PBO for 12 mths; both groups received MTX titrated to 15–20 mg per wk. Primary efficacy outcomes in the first 12 mths were Disease Activity Score 28 (C-reactive protein) remission (DAS28-CRP score <2.6) and joint damage progression (assessed by Genant-modified Sharp total score [TS]). Secondary efficacy outcomes at Mth 12 were ACR 50 response, DAS28-CRP LDAS (≤3.2) and improvement in physical function measured using the Health Assessment Questionnaire-disability index (HAQ-DI). Safety was monitored throughout the study. Results: In the overall population, 509 pts were randomly assigned to IV ABA+MTX (n=256) or PBO+MTX (n=253). In the subset of pts with very early RA, 167 were treated with IV ABA+MTX vs 157 treated with PBO+MTX. Mean (SD) disease duration at baseline was 6.5 (7.3) mths in the overall population vs 1.7 (2.0) mths in the very early RA subset. Baseline characteristics were otherwise similar between the two treatment groups and the overall population. The key efficacy results (Table) were similar between this subset of pts and the overall population. Safety profiles were also similar in both groups: ≤6 mths: adverse events (AEs), ABA 147 (88%), PBO 135 (86.0%); serious adverse events (SAEs), ABA 16 (9.6%), PBO 15 (9.6%): overall population: AEs, ABA 217 (84.8%), PBO 211 (83.4%); SAEs, ABA 20 (7.8%), PBO 20 (7.9%). Conclusions: This post-hoc analysis showed that efficacy and safety of IV abatacept+MTX in a subset of pts with very early RA (≤6 mths disease duration) were better than the PBO+MTX group, consistent with those with longer duration. Disclosure of Interest: R. Westhovens Grant/Research support from: Roche, UCB, Inc., Consultant for: Bristol-Myers Squibb, Centocor, Inc., Roche, Schering-Plough, Speakers Bureau: Bristol-Myers Squibb, J. Wollenhaupt Consultant for: Bristol-Myers Squibb, J. Gomez Reino: None Declared, W. Grassi Grant/Research support from: Abbott, Brystol Myers Squibb, Esaote, General Electric, Menarini, Merck Sharp & Dohme, Pfizer, Roche, Schering-Plough, UCB, Consultant for: Abbott, Brystol Myers Squibb, Esaote, General Electric, Menarini, Merck Sharp & Dohme, Pfizer, Roche, Schering-Plough, UCB, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Gaillez Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Poncet: None Declared, A. Elegbe Employee of: Bristol-Myers Squibb, J. Smolen Grant/Research support from: Abbott Laboratories, Bristol-Myers Squibb, Hoffmann-La Roche, Inc., Schering-Plough, UCB, Inc., Pfizer, Consultant for: bbott Laboratories, Amgen Inc., AstraZeneca, Bristol-Myers Squibb, Centocor, Inc., Eli Lilly and Company, Merck, Novo Nordisk, Roche, sanofi-aventis, UCB, Inc.